ANALISIS BIBLIOMETRIK TREN GLOBAL DALAM RISET TEKNOLOGI PENDIDIKAN ISLAM PADA PUBLIKASI SCOPUS 2015–2025 - Nabilah Putri; Shobah (LPPM STAI Muhammadiyah Probolinggo, 2026)
The acceleration of educational digitalization over the past decade has significantly transformed Islamic Religious Education (PAI). However, comprehensive mapping of global research trends on educational technology within the context of PAI remains limited. This study aims to analyze publication trends, collaboration patterns, author productivity, journal distribution, influential articles, and thematic dynamics of technology-related research in PAI from 2015 to 2025. A bibliometric approach was employed using Scopus-indexed data, resulting in 262 articles selected through the PRISMA protocol. Data were analyzed using the Bibliometrix-Biblioshiny (R) package, including performance analysis, co-authorship networks, co-citation analysis, keyword co-occurrence, and thematic mapping. The findings reveal a significant increase in publications, particularly after the COVID-19 pandemic, with Indonesia emerging as the leading contributor within the global collaboration network. Dominant themes include educational technology, Islamic education, digital literacy, and e-learning integration, primarily classified as motor themes and basic themes. The collaboration structure demonstrates a semi-centralized network with Indonesia acting as the main hub. The study concludes that research on technology in PAI is increasingly interdisciplinary, integrating pedagogical, digital, and spiritual dimensions. The findings contribute a comprehensive global literature map and conceptual foundation to support inclusive and sustainable digital innovation and policy development in Islamic education.